Digital Transformation in Supply Chain Management: A Literature Review - Rizky Budi Pratama; Suheri Efendi; Wahyu Indra Susila; Alwansyah Putra; Vidi Agung Fragastia; Nita Marikena (LPPM Universitas Potensi Utama, 2025)
In the era of globalization and increasingly complex industrial competition, the digitalization of Supply Chain Management (SCM) has become a key strategy for enhancing efficiency, responsiveness, and competitive advantage. This study aims to examine the role of digital transformation in supply chain management through a literature review of 20 national and international journal articles published between 2017 and 2025. The analysis reveals that SCM digitalization—through the integration of technologies such as the Internet of Things (IoT), Big Data Analytics, Artificial Intelligence (AI), and blockchain—can significantly improve data visibility, accelerate real-time information flow, and support analytics-based decision-making. This transformation not only drives operational efficiency but also strengthens collaboration and supply chain resilience. However, the adoption of digital technologies still faces various challenges, including infrastructure limitations, high investment costs, and insufficient human resource readiness. Several studies also highlight that the impact of digitalization on product quality and sustainability is not yet optimal without improvements in quality management systems and supportive regulations. Therefore, sustainable and context-specific implementation strategies, as well as collaboration among government, industry, and academia, are essential. This study recommends further exploration of inclusive digital adoption models, cybersecurity reinforcement, and the integration of digital SCM aligned with sustainability and resilience principles to face global disruptions. With the right approach, SCM digitalization can serve as a strategic foundation for building adaptive, efficient, and competitive supply chains in the Industry 4.0 era.